Electrophilic Organobismuth Dication Catalyzes Carbonyl Hydrosilylation. Issue 56 (8th September 2020) - Kannan, Ramkumar; Balasubramaniam, Selvakumar; Kumar, Sandeep; Chambenahalli, Raju; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract: Bismuth compounds are gaining importance as potential alternatives to transition‐metal complexes and electron deficient lighter p‐block compounds in homogeneous catalysis. Computational analysis on the two‐coordinate [(Me2 NC6 H4 )Bi] 2+ possessing three electrophilic sites is experimentally evidenced by the isolation of [Me2 NC6 H4 Bi{OP(NMe2 )3 }3 ][B(3, 5‐C6 H3 Cl2 )4 ]2 . These observations led us to generate dicationic organobismuth catalyst, [(Me2 NC6 H4 )Bi(L)3 ] 2+ (L=aldehyde/ketone), evidenced by NMR spectroscopy in solution and by single‐crystal X‐ray diffraction in the solid state. It efficiently catalyzes hydrosilylation of aldehydes and ketones resulting in silyl ethers as the only products in high yields. Our investigations support a carbonyl activation mechanism at the bismuth center followed by Si−H addition. Abstract : The first bismuth‐catalyzed carbonyl hydrosilylation is presented. The catalytically active electrophilic dicationic bismuth species [(Me2 NC6 H4 )Bi(L)3 ] 2+ (L=aldehyde/ketone) is characterized both in solution and in the solid state. Control experiments and computation studies support a carbonyl activation mechanism at bismuth followed by silane addition.